2006
DOI: 10.1001/archneur.63.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variability Among Adult Siblings With Sjögren-Larsson Syndrome

Abstract: Background: Sjögren-Larsson syndrome (SLS) is an early childhood-onset disorder with ichthyosis, mental retardation, spastic paraparesis, macular dystrophy, and leukoencephalopathy caused by the deficiency of fatty aldehyde dehydrogenase due to mutations in the ALDH3A2 gene (the gene that encodes microsomal fatty aldehyde dehydrogenase). Cerebral proton magnetic resonance spectroscopy in those with SLS demonstrates an abnormal white matter peak at 1.3 ppm, consistent with long-chain fatty alcohol accumulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 6 publications
1
30
0
3
Order By: Relevance
“…The Swedish patients who carry an identical ALDH3A2 allele seem to have a limited spectrum of phenotypic variation [2,7]. Nevertheless, significant variation in neurologic disease has been reported in a large Arab family with 6 affected siblings [30]. Among 9 Brazilian patients homozygous for c. 1108-1G>C, there were some differences in the presence of pruritus, retinal glistening white dots and photophobia [29].…”
Section: Aldh3a2 Mutations and Sequence Variations In Slsmentioning
confidence: 99%
“…The Swedish patients who carry an identical ALDH3A2 allele seem to have a limited spectrum of phenotypic variation [2,7]. Nevertheless, significant variation in neurologic disease has been reported in a large Arab family with 6 affected siblings [30]. Among 9 Brazilian patients homozygous for c. 1108-1G>C, there were some differences in the presence of pruritus, retinal glistening white dots and photophobia [29].…”
Section: Aldh3a2 Mutations and Sequence Variations In Slsmentioning
confidence: 99%
“…15 Most mutations are unique to each affected family 6 and clinical variations, even among siblings, may be due to unknown genetic or environmental factors. 20 The possibility of genetic heterogeneity is not excluded 21 and missence mutations comprise the largest class of the many mutations. 22,23 Biochemistry The exact pathogenesis is uncertain, but the deficiency of fatty aldehyde dehydrogenase in this syndrome impairs the process which catalyzes the oxidation of medium-and longchain fatty aldehydes.…”
Section: Diagnosismentioning
confidence: 99%
“…They also demonstrated that the spectral abnormalities emerged during the first years after birth and then stabilized. Lossos et al [124] investigated 6 patients with early childhood onset SL aged 16-36 years. There was considerable phenotype variability with a decrease in the lipid peak with age.…”
Section: Sjogren -Larsson Syndromementioning
confidence: 99%